Activity profile of elite Gaelic football referees during competitive match play - Brady, A. J.; Moyna, N. M.; Scriney, M.; McCarren, A. (Science and Medicine in Football, 2023)
The purpose of this study was to examine the activity profile of elite Gaelic football referees (GFR) and to examine temporal changes between the first and second half and across the four quarters. Global positioning systems technology (10-Hz) was used to collect activity data during 202 competitive games from 23 elite GFR. Relative distance, peak running speed and relative distance covered in six movement categories [very low-speed movement (VLSM) (<0.70 m·s-1), walking (=0.70-1.65 m·s-1), low-speed running (LSR) (=1.66-3.27 m·s-1), moderate-speed running (MSR) (=3.28-4.86 m·s-1), high-speed running (HSR) (=4.87-6.48 m·s-1), very high-speed running (VHSR) (=6.49 m·s-1)] were examined during the full game, first and second half, and across the four quarters. The relative distance covered was 122.6 ± 8.4 m·min-1, with 13.1 ± 4.9 m·min-1 of HSR and VHSR. The peak running speed was 6.75 ± 0.49 m·s-1. The relative (ES=0.60), MSR (ES=0.50) and HSR (ES=0.14) distance was higher in the first half than the second half. A higher relative (ES=0.62-0.91) and HSR (ES=0.51-0.61) distance was found in the first quarter than any other period. No differences in HSR distance were found between the second, third and fourth quarters (ES=0.04-0.10). This study provides, for the first time, a detailed insight into the activity profile of elite GFR during competitive games and demonstrates the demanding, intermittent nature of elite refereeing in Gaelic football. This information may be used as a framework for coaches to design training programmes specific to GFR.